Meningkatkan Interaksi Sosial Pada Orang dengan Disabilitas Melalui Media Musik Dangdut Koplo di Sentra Terpadu Kartini Temanggung: Pengabdian Masyarakat - Rahmawati, Meliana; Wulandari, Sarah Putri; Laila, Yulidar RP (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
This project aims to enhance social interaction among individuals with disabilities residing in the Sentra Terpadu Kartini Temanggung. Dangdut music serves as one of the medium for facilitating interaction among individuals within the group. Activities to improve social interaction among disabled individuals need to be presented in an enjoyable manner, one of which is through simple games involving physical movement. The result of this activities indicate that the process of interaction becomes easier when using media that align with the preferences of a particular group, such as dancing and singing along to dangdut music.